2013
DOI: 10.5751/es-05260-180131
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Map Ecosystem Functions to Support Ecosystem Services Assessments

Abstract: ABSTRACT. The project developed and trialed a method of mapping ecosystem functions in South East Queensland using biophysical data layers in preference to land use surrogates. Biophysical data and surrogates were identified for 19 ecosystem functions and maps were produced for each. Data layers for each ecosystem function were standardized for mapping purposes using existing expert advice or data quantiling. Two versions of the total ecosystem function overlap maps were also produced, showing areas of high ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 64 publications
0
26
0
1
Order By: Relevance
“…We consider a total of 7 ecosystem services, represented by 9 indicators (Table 3.1). In order for each ecosystem service to contribute equally to the analysis, and following the method of Petter et al (2013), we standardized the data by reclassifying each service into a quantile split, producing a range of scores from 1 to 5 (five meaning high supply of a specific service). We then summed the 9 indicators to produce a map of "total" ecosystem services supply across Europe (Fig.…”
Section: The Spatial Distribution Of Ecosystem Services In Europementioning
confidence: 99%
“…We consider a total of 7 ecosystem services, represented by 9 indicators (Table 3.1). In order for each ecosystem service to contribute equally to the analysis, and following the method of Petter et al (2013), we standardized the data by reclassifying each service into a quantile split, producing a range of scores from 1 to 5 (five meaning high supply of a specific service). We then summed the 9 indicators to produce a map of "total" ecosystem services supply across Europe (Fig.…”
Section: The Spatial Distribution Of Ecosystem Services In Europementioning
confidence: 99%
“…The databases used allow the quantifying of intervals of indicator values as reference for site-specific evaluations of ecosystem integrity. Considering other investigations that aim to analyse ecosystem integrity (Andreasen et al, 2001;Balvanera et al, 2006;Cairns, 1977;Carignan and Villard, 2002;EEA, 2012;Egoh et al, 2012;Faber-Langendoen et al, 2012a,b;EU, 2014;Petter et al, 2013;Stoll et al, 2015;Tierney et al, 2009;Vose et al, 2012;Wulff et al, 2012), the mapping and analysis of ecosystem types across space and time in combination with ecosystem type-/site-specific reference intervals for functional and structural indicators broadens and deepens ecosystem integrity assessments. Climate change and N deposition are significant driving forces shifting ecosystems toward modified or even completely changed states.…”
Section: Specific Appraisalmentioning
confidence: 99%
“…The possibility of reduced ecosystem function is increased as more species are lost due to reductions in substitutability. Thus, biodiversity and ecosystem functions are codependent, and therefore, biodiversity is vital to maintaining functioning ecosystems and vice versa (Maynard et al, 2010(Maynard et al, , 2011Midgley, 2012;Petter et al, 2013). Under action 5 of the EU Biodiversity Strategy to 2020, the condition of ecosystems and their services should be mapped and assessed across Europe.…”
mentioning
confidence: 99%
“…, Petter et al. ). Studies concerned with existing landscape configurations have demonstrated that the spatial distributions of ecosystem functions, services, and biodiversity often do not overlap extensively, and many services show trade‐offs or no positive relationship (Chan et al.…”
Section: Introductionmentioning
confidence: 99%